The Relationship between Nutrition Aware Family Behavior and the Incidence of Stunting in Toddlers in the Ikur Koto Health Center Working Area in 2023 - Fitri Rahmah; Nurul Prihastita Rizyana; Yulia (Alifah Health Science Symposium Proceeding, 2023)
The prevalence of stunting in Indonesia was high at 26.92% in 2020. The highest stunting rate at the Puskesmas in Padang City is the Ikur Koto Puskesmas (16.0%). Nutrition-conscious family behavior is one of the efforts to overcome stunting. The purpose of this study was to determine the relationship between nutrition-conscious family behavior and the incidence of stunting in the working area of Puskesmas Ikur Koto in 2023. The research method used is quantitative research with a cross sectional design. The study was conducted in March-August 2023. This research approached 91 respondents used the simple random sampling method. Data was collected by interview using questioner and measurement with microtoise. Data analysis with chi-square statistical test. The results showed that (57.1%) toddlers were stunted. (51.6%) families do not behave nutritionally consciously. Based on statistical tests, it was found that there is a significant relationship between nutrition conscious family behavior and the incidence of stunting in toddlers in the Ikur Koto Health Center Working Area in 2023 (ρ-value = 0.001). This study suggest that the Ikur Koto Health care center would be providing nutrition consultations to mothers of toddlers, Health Center Ikur Koto need provide a nutrition conscious family surveys every year, increase counseling, conduct home visits for toddlers who have not received Vitamin A supplements, provide additional food and conduct balanced food cooking demonstrations.